Molecular mechanisms of glycogen particle assembly in Escherichia coli. (1st January 2023) - Li, Fen; Wang, Meng-Meng; Liu, Qing-Hua; Ma, Zhang-Wen; Wang, Jun-Jiao; Wang, Zi-Yi; Tang, Jia-Wei; Lyu, Jing-Wen; Zhu, Zuo-Bin; Wang, Liang
Abstract: It has been reported that glycogen in Escherichia coli has two structural states, that is, fragility and stability, which alters dynamically. However, molecular mechanisms behind the structural alterations are not fully understood. In this study, we focused on the potential roles of two important glycogen degradation enzymes, glycogen phosphorylase ( glgP ) and glycogen debranching enzyme ( glgX ), in glycogen structural alterations. The fine molecular structure of glycogen particles in Escherichia coli and three mutants (Δ glgP, Δ glgX and Δ glgP /Δ glgX ) were examined, which showed that glycogen in E. coli Δ glgP and E. coli Δ glgP /Δ glgX were consistently fragile while being consistently stable in E. coli Δ glgX, indicating the dominant role of GP in glycogen structural stability control. In sum, our study concludes that glycogen phosphorylase is essential in glycogen structural stability, leading to molecular insights into structural assembly of glycogen particles in E. coli . Graphical abstract: Unlabelled Image